Mengkaji Kebijakan Hukum Pidana Pencegahan Penyebaran Virus Covid-19 di Indonesia - Hasanal Mulkan; Susiana Kifli (Wajah Hukum, 2022)
The right of the community to live in peace and prosperity was guaranteed by the government in the Republic of Indonesia's 1945 Constitution. The government must coordinate better and convene all necessary stakeholders in order to stop the Covid-19 virus from spreading throughout Indonesia. The current issue is the criminal law policy. To battle the epidemic, this kind of normative legal research takes an analytical, conceptual, and legislative approach. When laws or regulations have been passed into legal products by government organizations, law enforcement is a technique to put the will into action. When enforcing laws during a time of emergency, the police will apply criminal punishments; however, they must also educate the public and protect them legally when they use repressive measures. This will be done through the Chief of Police's Declaration.